Rural-urban and gender differences in the association between community care services and elderly individuals' mental health: a case from Shaanxi Province, China - Liu Yang; Lijian Wang; Xiuliang Dai (BMC, 2021)
Abstract Background While community care services have been developing rapidly as a new way to meet the growing demands of elderly individuals in China, their health benefits are virtually unknown. Thus, the aim of this study was to examine the Chinese elderly individuals' utilisation of community care services and its association with the mental health with comparing rural-urban and gender differences. Methods For this 2019 cross-sectional study, 687 elderly people from 7 counties (districts) of China's Shaanxi province were enrolled. Respondents' mental health level was assessed using a self-reported mental health measure. Four categories of community care services utilisation were examined: daily care services, medical care services, social and recreational services and spiritual comfort services. The binary logistic regression model was used in examining the association between community care services utilisation and mental health. Results Our results showed that there was a noted difference in mental health level between the male and female groups. Utilisation of medical care services and social and recreational services was significantly higher in the rural group than that in the urban group. Regression analysis showed that utilisation of daily care services (β = 0.809, p = 0.008) and social and recreational service (β = 0.526, p = 0.035) was significantly and positively associated with elderly individuals' mental health level. Specifically, daily care services utilisation predicted a better mental health of the rural elderly (β = 1.051, p = 0.036) and the male elderly (β = 1.133, p = 0.053), while social and recreational services utilisation predicted a better mental health of the urban elderly (β = 0.927, p = 0.008) and the female elderly (β = 0.864, p = 0.007). Conclusions Our findings indicated varied levels of community care services utilisation and mental health are common among the elderly people in China. Community care services utilisation has a positive, albeit selective, association with elderly individuals' mental health. Further policies should strengthen the equitable development of high-quality community care services in urban and rural areas to improve the mental health of elderly individuals, and focus more on gender differences in terms of community care services needs.